Soziale Medien - Ein (kosmo-politischer) Erscheinungsraum? - Ossino, Vanessa (HannahArendt.net, 2022)
The article considers social media along Hannah Arendt’s conceptual framework of a space of appearance and addresses the question of what form of togetherness is suitable for social media and whether plurality in Arendt’s sense is possible in social media. Here, Arendt is further thought through in the light of a phenomenological reading, whereby the intersubjective ‘in-between’ of worldliness comes into focus. First, the contribution takes on Arendt’s concept of world, which, according to the argumentation, only reaches its full maturity following her philosophy of appearance and her theory of intersubjectivity. Subsequently, the tendency toward self-representation in social media is examined to determine whether it closes off a plural space of appearance of social media from the outset. It is argued that while social media imply the possibility of a plural space of appearance, their actuality and infrastructure often obscure the emergence of the Arendtian ‘who’ of someone and thus the virtual actions and speech of persons are exposed to the constant danger of anonymity, which would consequently mean the obstruction of a lived plurality in public appearance spaces.